Shape Optimization and Hydraulic Characteristics Analysis of Unilateral Divergent Stilling Basin - SHI Linping; LIAO Zhiying; XIE Zhigao; ZHOU Xuncheng; TU Xiangyang (Renmin Zhujiang)
The spillway of Dongchong Reservoir adopts an engineering scheme of spillway step energy dissipation and downstream stilling basin underflow. However, due to the limitations of terrain and geological conditions, the width of the stilling basin is small, and the angle between it and the river is 145°; meanwhile, the current downstream traffic bridge hinders flood discharge, resulting in many unfavorable factors. For the original scheme, the discharge entering the stilling basin makes the water surface fluctuate greatly, and the water flow out of the basin accelerates significantly. The main flow in the river is concentrated, and a large-scale backflow area is formed on the left of the upstream traffic bridge. This paper optimizes the layout scheme of the stilling basin through hydraulic model tests. The results show that through measures such as deepening the stilling basin, installing T-shaped piers in the front section of the basin, shifting the left side wall of the stilling basin to the left, and lowering the tail-weir and creating a reverse slope towards the river, etc., the water flow pattern is significantly improved. After the discharge enters the basin, the fluctuation amplitude of the water surface decreases, and the water flow out of the basin no longer accelerates. The water flow in the river is dispersed and the flow velocity falls. The research results can provide a reference for similar projects.